Pull-Out Resistance of Sand-Geosynthetics Reinforcement - Ismail, M. K. A.; Joohari, M. I.; Habulat, A.; Azizan, F. A. (International Journal of Integrated Engineering, 2021)
Geosynthetics are widely used in earth retaining structures such as steep slope and earth retaining wall. The stability of the earth retaining structures depends on the interaction between geosynthetics and soil at the reinforced area known as reinforcement mechanism. The reinforcement mechanism of the soil reinforced structure usually difficult to be analysed thoroughly. It is because the preliminary study on the pull-out resistance and durability of the reinforcement material is not taking into account before it has been used to the site location especially in Malaysian practises. Less supervision and the assessment after the installation of the reinforcement materials also contributed to the failure of the soil reinforcement. In this paper, the laboratory model was used to imply the real condition of the soil reinforced structure using pull-out test. A standard pull-out test was carried out by using geotextile and geogrid reinforcing elements embedded into silica sand of size D50=1.357 mm and D50=0.571 mm subjected to normal pressures of 100 kPa, 150 kPa and 200 kPa. Comparative result and analysis showed that the geotextile reinforcement give more resistance rather than geogrid reinforcement under high normal pressure.